Geographic and Seasonal Variation of Vitamin D: A Retrospective Study in Two Centers of Nepal - Sedhain, Arun; Bhattarai, Gandhi R; Yadav, Sanjaya Raya; Pandey, Bhupendra Raj; Pant, Thakur Prasad (Journal of Nepal Health Research Council, 2020)
Background: Vitamin D deficiency is a common problem in many countries throughout the world. This study aimed at understanding the status of vitamin D deficiency in relation to age, gender, geography and season among relatively bigger numbers of population residing in central and western regions of Nepal.Methods: This retrospective cross-sectional study was carried out by reviewing the records of vitamin D tests in two centers of Nepal- namely united reference laboratories at Pokhara and Chitwan Medical College at Chitwan. A total of 3320 individuals who were tested for clinical suspicion of vitamin D deficiency over a period of one year were included in the study. Results: Mean vitamin D level was 18.7 ng/mL. Majority of subjects tested for vitamin D were females (71.36 %) with female to male ratio of 2.49:1. Hypovitaminosis D (? 30 ng/mL) was found in 84.5% subjects and was moderate to severely deficit (<10 ng/mL) in 25.9% of subjects. Status of hypovitaminosis D was found to be less in ?50 years (79.9%) than the younger subjects (89.9% in ?18 years and 87.0% in 19-49 years age group). Vitamin D deficiency was found lower in hills districts (80.8% vs 89.7% in the plains), which was found to be more pronounced during winter through summer seasons as compared to fall season.Conclusions: Population residing in plain areas and summer, spring and winter season are found to have increased problem of Hypovitaminosis D. It is also found to be common among younger children and female of reproductive age group. We have also found out the increased problem of hypovitaminosis D among population residing in the plain areas than in the hills especially in the summer, spring and winter season.Keywords: Geographic variation; hypovitaminosis D; Nepal